2009
DOI: 10.1016/j.ejvs.2008.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Health-related Quality of Life with the Dutch Translated Aberdeen Varicose Vein Questionnaire before and after Treatment

Abstract: This study established the use of the Dutch translated AVVQ as a valid, health-related quality of life (QOL) questionnaire for measuring QOL before and after treatment in patients with clinical-severity classes 1-6 venous disease of the leg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 5 publications
1
32
0
1
Order By: Relevance
“…Improvements in QoL did not differ significantly between groups, which could be either because both interventions were effective (or ineffective) or because EQ-5D-5L was not sensitive enough. Large scale studies involving the "Patient Reported Outcome Measures" [23], used by the National Health Service in England, show that patient-administered disease-specific QoL tools [24][25][26] are more sensitive than EQ-5D. Disease-specific tools were not used in this study, partly because they are not available for the large variety of diseases, and partly because existing tools have different scales and variable validity.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in QoL did not differ significantly between groups, which could be either because both interventions were effective (or ineffective) or because EQ-5D-5L was not sensitive enough. Large scale studies involving the "Patient Reported Outcome Measures" [23], used by the National Health Service in England, show that patient-administered disease-specific QoL tools [24][25][26] are more sensitive than EQ-5D. Disease-specific tools were not used in this study, partly because they are not available for the large variety of diseases, and partly because existing tools have different scales and variable validity.…”
Section: Discussionmentioning
confidence: 99%
“…Only 4 of 13 items address the psychological impact of varicose veins, especially the functioning domain. 11,12 Therefore, the AVVQ reflects the clinical disease severity and less significantly the impact of the disease on a patient's life. In contrast to the AVVQ, the CIVIQ has focussed more on the psychosocial impact of venous disease of the lower limbs (i.e., its effect on everyday life).…”
mentioning
confidence: 99%
“…This study therefore concluded that treatment of venous disease can improve quality of life. 20 In this study there was a statistically significant difference in the functional capacity domain, thereby showing that wearing elastic stockings is an effective treatment that improves quality of life, in agreement with the study published by Klem et al 20 Studies have shown a significant association between Quality of Life and CVD and, employing the SF-36, it has been found that even in the early phases this disease has a substantial impact on the physical dimensions of health, manifest as functional limitations and difficulties with daily activities. 21 The findings of the present study show a significant difference in the SF-36 functional capacity domain with patients who wore elastic stockings scoring higher than those who did not, indicating better quality of life with relation to this domain.…”
Section: Discussionmentioning
confidence: 99%